Floods and Droughts - Camilloni, Ines Angela (2020)
Several multi-scale climate change adaptation measures with regard to droughts and floods are already being implemented in Latin America. These include improving the quality of forecasts, early warning systems and climate information services, plans for reducing vulnerability and increasing the resilience of the population, strategic infrastructure and production systems, and the conservation and sustainable use of ecosystems and their environmental services. Yet there are still institutional, regulatory, administrative, economic, and social obstacles that can delay the implementation of some of these measures. consequently, to accelerate the adaptation process, countries will need to improve their planning and response capacities, as well as their disaster management and insurance schemes.